Age Induced Nitroso-Redox Imbalance Leads to Subclinical Hypogonadism in Male Mice - Lee, John Alden; Kuchakulla, Manish; Arora, Himanshu; Kulandavelu, Shathiyah; Gonzalez, Evert; Masterson, Thomas A.; Hare, Joshua M.; Kaiser, Ursula B.; Ramasamy, Ranjith (Frontiers in Endocrinology, 2019)
Objective: The cause of age-related changes in testosterone remains unclear. We hypothesized that increased nitroso-redox imbalance with aging could affect testosterone production. Materials and Methods: We measured several markers of nitroso-redox imbalance (4-HNE, 3-NT, and NT) in serum of S-nitrosoglutathione reductase knock out (GSNOR KO) mice that have increased nitroso-redox imbalance and compared these to wild-type (WT) mice. We evaluated the impact of age-induced nitroso-redox imbalance on serum luteinizing hormone (LH) and testosterone (T) in WT young (<2 months), middle-aged (2–6 months), and aged (>12 months) mice. Finally, to elucidate the susceptibility of testes to nitroso-redox imbalance, we measured 4-HNE protein levels in the testes of WT and KO mice. Results: We identified 4-HNE as a reliable marker of nitroso-redox imbalance, as evidenced by increased protein levels in serum of GSNOR KO mice compared with WT mice. We demonstrated that 4-HNE serum protein levels increase in WT mice with age but do not accumulate in the testes. We also found that T levels were similar in all age groups. Interestingly, we found that serum LH levels in aged and middle-aged mice were increased when compared to young mice (n = 5) consistent with the phenotype of subclinical hypogonadism. Conclusions: Increased serum 4-HNE and LH levels without changes in T with age suggest that nitroso-redox imbalance is associated with subclinical hypogonadism in aged mice. Recognizing the relationship and etiology of a currently poorly understood classification of hypogonadism could be a paradigm shift in how age-related testosterone change is diagnosed and treated.